Circadian oscillations in Trichoderma atroviride and the role of core clock components in secondary metabolism, development, and mycoparasitism against the phytopathogen Botrytis cinerea - Marlene Henríquez-Urrutia; Rebecca Spanner; Consuelo Olivares-Yánez; Aldo Seguel-Avello; Rodrigo Pérez-Lara; Hector Guillén-Alonso; Robert Winkler; Alfredo Herrera-Estrella; Paulo Canessa; Luis F Larrondo (eLife, 2022)
Circadian clocks are important for an individual’s fitness, and recent studies have underlined their role in the outcome of biological interactions. However, the relevance of circadian clocks in fungal–fungal interactions remains largely unexplored. We sought to characterize a functional clock in the biocontrol agent Trichoderma atroviride to assess its importance in the mycoparasitic interaction against the phytopathogen Botrytis cinerea. Thus, we confirmed the existence of circadian rhythms in T. atroviride, which are temperature-compensated and modulated by environmental cues such as light and temperature. Nevertheless, the presence of such molecular rhythms appears to be highly dependent on the nutritional composition of the media. Complementation of a clock null (Δfrq) Neurospora crassa strain with the T. atroviride-negative clock component (tafrq) restored core clock function, with the same period observed in the latter fungus, confirming the role of tafrq as a bona fide core clock component. Confrontation assays between wild-type and clock mutant strains of T. atroviride and B. cinerea, in constant light or darkness, revealed an inhibitory effect of light on T. atroviride’s mycoparasitic capabilities. Interestingly, when confrontation assays were performed under light/dark cycles, T. atroviride’s overgrowth capacity was enhanced when inoculations were at dawn compared to dusk. Deleting the core clock-negative element FRQ in B. cinerea, but not in T. atroviride, was vital for the daily differential phenotype, suggesting that the B. cinerea clock has a more significant influence on the result of this interaction. Additionally, we observed that T. atroviride clock components largely modulate development and secondary metabolism in this fungus, including the rhythmic production of distinct volatile organic compounds (VOCs). Thus, this study provides evidence on how clock components impact diverse aspects of T. atroviride lifestyle and how daily changes modulate fungal interactions and dynamics.